Treatment of rhinitis - Samoliński, Bolesław; Komorowski, Jarosław (Przewodnik Lekarza/Guide for GPs, 2006)
General practitioner should make the diagnostic and order therapeutic procedures in allergic rhinitis patient. Consultations are necessary when some difficulties arise, then an allergy specialist should solve the problems. Only specific immunotherapy is reserved for the allergologist. The aim of this paper is also to describe present guidelines of differentials diagnosis and treatment of chronic rhinosinusitis. According to recent publications the patomechanism of the inflammation of the nasal mucosa plays important role. Purulent chronic rhinosinusitis is the stage Th1 immunological response. Cytokin profile of NARES, allergic rhinitis and nasal polyps is typical for the Th2 response. Although immunological parameters play an important role in differential diagnosis, the clinical picture is the most important for diagnosis and planning treatment in every day practise. The paper also present the algorithm of chronic rhinosinusitis diagnosis and treatment following EAACI and ERS guidelines.